2020
DOI: 10.21203/rs.3.rs-36937/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence, Serotyping and Antimicrobial Susceptibility Profile of Avibacterium Paragallinarum Isolated From Local Commercial Poultry of Balochistan

Abstract: Abstract Background Infectious coryza (IC) caused by Avibacterium paragallinarum, a Gram negative, non-motile coccobacilli, is a severe upper respiratory tract disease of poultry. This study aimed to report on the isolation rate and serotyping of Avibacterium paragallinarum causing Infectious Coryza (IC) in commercial layer poultry in Balochistan. Results Total 500 samples were collected from IC-suspected or recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On the other hand, the overall levels of resistance for ciprofloxacin, and tetracycline were 75 and 25%, respectively. Whereas a previous study revealed maximum resistance rates of A. paragallinarum against both antimicrobials (41).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…On the other hand, the overall levels of resistance for ciprofloxacin, and tetracycline were 75 and 25%, respectively. Whereas a previous study revealed maximum resistance rates of A. paragallinarum against both antimicrobials (41).…”
Section: Discussionmentioning
confidence: 55%
“…paragallinarum serotype C isolates (n = 4) were intermediate susceptible to ciprofloxacin but susceptible to tetracycline. While a previous study stated that 18.1% and 2.7% of serotype C were resistant to tetracycline and ciprofloxacin, respectively (41).…”
Section: Discussionmentioning
confidence: 93%